First trimester bleeding and pregnancy outcome - Kamble, Pradnya Digambar; Bava, Amarjeetkaur; Shukla, Mansi; Nandanvar, Y. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The outcome of first trimester vaginal bleeding is a matter of debate. This study sought to determine the maternal and perinatal outcome in patients presenting with first trimester vaginal bleeding. Methods: This prospective observational study was done on 1007 women with first trimester vaginal bleeding at a tertiary care hospital in Mumbai over a period of one year. A detailed history was taken and USG was done to confirm diagnosis. All these patients were evaluated for the outcomes including threatened abortions, spontaneous, complete or incomplete abortions, sub-chorionic hematoma, Intra-uterine Fetal Demise, missed abortions, second and third trimester bleeding, Intra-uterine Growth Restriction, premature rupture of membranes and preterm deliveries. Results: Out of the 11835 confinements 1007 patients presented with first trimester vaginal bleeding. The incidence was highest (52.3%) in the age group of 21-30 years. 63.9% primigravidas presented with first trimester bleeding as compared to 36.1% of multigravidas. It was seen that 76.9% patients who presented before 6 weeks aborted whereas only 7% patients who presented after 10 weeks aborted. Out of the 163 patients that continued pregnancy after first trimester vaginal bleeding 1.8% had a second trimester abortion, 15.3% went into preterm labour 6.75% has premature rupture of membranes and 1.8% had antepartum hemorrhage. Conclusions: According to the results of present study, first trimester vaginal bleeding predicts auxiliary maternal and fetal complications. Also, as the clinical intermediation has an important role in continuance of pregnancy and in reducing the fetal complications precise management and planning by physician is important.